THE MODEL FOR SELECTING THE OPTIMAL INTERCITY SCHEME FOR PACKAGED CARGO DELIVERY WITH THE USE OF ROAD TRANSPORT - Nagornyi, Ye.; Naumov, V.; Shulika, O.; Нагорний, Є. В.; Наумов, В. С.; Шуліка, О. О.; Нагорный, Е. В.; Шулика, О. А. (Харьковский национальный автомобильно-дорожный университет, 2014)
Planning and implementation of the process of packaged cargo delivery by road transport are based on the transport and technological schemes of delivery. The optimal scheme choice allows providing the maximal cumulative effect of all participants of the transport process. The total costs of the delivery process participants have been proposed as the criterion for determining the optimal transport and technological delivery scheme. The proposed approach to the formalization of the com-plete set of alternative variants of the packaged cargo delivery process in the intercity as a graph-model allows using the network optimization techniques.
МОДЕЛЬ ВИБОРУ ОПТИМАЛЬНОЇ ТРАНСПОРТНО-ТЕХНОЛОГІЧНОЇ СХЕМИ ДОСТАВКИ ТАРНО-ШТУЧНИХ ВАНТАЖІВ АВТОМОБІЛЬНИМ ТРАНСПОРТОМ У МІЖМІСЬКОМУ СПОЛУЧЕННІ
МОДЕЛЬ ВЫБОРА ОПТИМАЛЬНОЙ ТРАНСПОРТНО-ТЕХНОЛОГИЧЕСКОЙ СХЕМЫ ДОСТАВКИ ТАРНО-ШТУЧНЫХ ГРУЗОВ АВТОМОБИЛЬНЫМ ТРАНСПОРТОМ В МЕЖДУГОРОДНОМ СООБЩЕНИИ
Keywords: delivery process; packaged cargo; intercity transportation; road transport; процес доставки; тарно-штучні вантажі; міжміські перевезення; автомобільний транспорт; процесс доставки; тарно-штучный груз; междугородные перевозки; автомобильный транспорт; 656.073.28